Participatory mangrove planting as a coast abration disaster mitigation effort in Pasimarannu Village, Sinjai Regency - Ridha Alamsyah; Andi Liswahyuni; Uspar Uspar; Irfan Fauzi (University of Merdeka Malang, 2023)
Pasimarannu village as one of the villages experiencing coastal abrasion and threatening the settlements of residents living in coastal areas. During the high tide, several houses were submerged by sea water, and during the east and west seasons the wind was strong enough so that the high waves reached under the houses. Attention and effort are needed in anticipating the level of damage that will occur. The community service program is carried out by providing awareness and active participation of the community in protecting the coast through participatory mangrove planting. The method of implementing the activities consists of socialization and FGD on the implementation of the activity plan, Formation of Forest Farmer Groups (KTH), mangrove nurseries, participatory mangrove planting, embroidery, and maintenance, as well as program monitoring and evaluation. Technical activities involve extension workers and forestry technical personnel. The key to the success of this participatory planting is the right planting time to avoid the strong currents and waves in the east monsoon. Routine maintenance activities to anticipate and eradicate oyster pests that damage plants during the vulnerable phase, which is up to 4 months of planting.